Predictors for perceived competence of breast self-examination among undergraduate female students. - Kaushalya, K.A.D.S.; Thavalingaratinam, P.; Dematapitiya, B.R.V.H.K.; Minipura, D.K.A.T.S.R.; Ranathunga, S.R.; Kolambage, S.H.; Senarathna, W.L.S.S.; Asurakkoddy, T.A.; Herath, H.M.C.H. (University of Colombo, 2023)
Introduction: Breast cancer is the most common cancer among women in Sri Lanka, and Breast SelfExamination (BSE) has the potential to detect 90% of breast cancers. Despite the benefits of BSE, limited numbers of women engage in it, and many do not know how to perform it. According to the previous literature and Statistical findings related to breast cancer show that BSE is not popular among women in Sri Lanka. Objective: To explore the predictors on perceived competence for BSE among female undergraduates. Methods: The study was descriptive cross-sectional research conducted on 427 female undergraduate students from the Faculty of Nursing, Medicine, and Science at the University of Colombo. Data was collected through an online questionnaire and analyzed using SPSS software. Results: Approximately two-thirds of participants (67.2%) were between the ages of 20 and 25 years. The majority of the study’s participants were single (90.4%). Ethnically, 87.1% were Sinhalese, and the majority were Buddhist (77.3%). The study found a weak positive significant linear correlation between motivation for BSE (p< .05) and perceived competence and a moderate positive significant linear correlation between perceived competence and knowledge of BSE (p <.05). Additionally, Faculty, Academic year and participants’ religion were significantly associated with perceived competence in BSE (p<0.05). Conclusion: Motivation of BSE, Knowledge of BSE, Faculty, Academic year, and religion of the participants were the predictors for the perceived competence. The conclusion highlights the need for promoting BSE to reduce breast cancer mortality and further research to address the factors affecting BSE among female undergraduate students in Sri Lanka.
Keywords: Knowledge; Motivation; Breast self-examination; Perceived Competence